PENGELOLAAN SAMPAH MELALUI PEMBERDAYAAN POTENSI DESA - Linda Linda (Swadaya: Indonesian Journal of Community Empowerment, 2019)
This activity aims to provide the knowledge, training and assistance to the people Bakung Kidul village, District Jamblang, Cirebon regency, West Java province in managing waste through the development potential of the village. Implementation of community service is done by conducting a census to identify existing problems. Of the problems found further prioritize problems based on criteria ultrasound (Urgency, Seriousness, and Growth) were analyzed using these three elements. Having determined that the priority issues, then look for the root cause of the problem. To find the root cause of the problem used a causal diagram of Ishikawa (fish bone). Keywords: Mentoring, waste management, the census